An assessment of the potential of sustainable construction in Saudi Arabia with particular reference to the city of Mecca - Alshareef, Sultan (Trinity College (Dublin, Ireland). Department of Civil, Structural and Environmental Engineering, 2017)
Global construction industry is growing rapidly. Sustainable principles are applied in the developed world. However, these are absent in the majority of construction in the developing world. Saudi Arabia is the largest construction market in the Middle East therefore, there is an urgent need to consider sustainable construction principles in the country, especially in the major cities like Mecca (with more than one third of the overall Saudi construction). This research evidenced that there are limited attempts toward achieving sustainable construction across the country. It proposes sustainable solutions based on the literature review, questionnaire survey, personal interviews and the findings of a case study modelling in Mecca. The research also determines potential sustainable techniques suitable for the Saudi Arabian climate based on traditional and historic techniques. This work aims at drawing the attention of government and policy makers towards the importance of sustainability in construction and encouraging sustainable legislation.
Keywords: Civil, Structural and Environmental Engineering, Ph.D.; Ph.D. Trinity College Dublin, 2017